(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Today dental surgeries for cosmetic alterations have been increasing, considering that the anterior teeth are mainly seen when a person speaks or smiles, it makes it clear that these are essential actors in the aesthetics of a patient. However we must also worry about preserving and / or return of guides disclusion order to achieve a mutually protected occlusion. With technological advances that have occurred in this adhesion can be achieved by perfectly composed with a minimally invasive technique and lower cost resins. It is presented to view a patient who has just completed his orthodontic treatment, and which the specialist told her to be multiple cavities in molars, but to perform the initial review we have a serious cosmetic problem in the upper front teeth, is He offered to treat that patient problem through a diagnostic wax technique, Mock-up and subsequently performing through direct resin restorations. The purpose of presenting this clinical case illustrates a technique of modified Mock-up is useful both as a diagnostic and for different steps in the same restorative treatment tool.